2019
DOI: 10.1264/jsme2.me19033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Regulated by the Antitermination Factor NasT during Denitrification in <i>Bradyrhizobium diazoefficiens</i>

Abstract: The soybean symbiont Bradyrhizobium diazoefficiens grows anaerobically in the presence of nitrate using the denitrification pathway, which involves the nap, nir, nor, and nos genes. We previously showed that NasT acts as a transcription antitermination regulator for nap and nos gene expression. In the present study, we investigated the targets of NasT in B. diazoefficiens during denitrifying growth by performing transcription profiling with RNA-seq and quantitative reverse-transcription PCR. Most of the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…1B). Denitrification generally requires four enzymes: nitrate reductase (Nap), nitrite reductase (Nir), nitric oxide reductase (Nor), and N 2 O reductase (Nos) (Zumft, 1997;Jang et al, 2018;Sánchez et al, 2019). An examination of the genes of these four enzymes indicated that nos gene clusters encoding N 2 O reductase were consistently found in group D and W members (black circle in Fig.…”
Section: S3mentioning
confidence: 99%
“…1B). Denitrification generally requires four enzymes: nitrate reductase (Nap), nitrite reductase (Nir), nitric oxide reductase (Nor), and N 2 O reductase (Nos) (Zumft, 1997;Jang et al, 2018;Sánchez et al, 2019). An examination of the genes of these four enzymes indicated that nos gene clusters encoding N 2 O reductase were consistently found in group D and W members (black circle in Fig.…”
Section: S3mentioning
confidence: 99%